2020
DOI: 10.1186/s12886-020-01498-7
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Ranibizumab with macular laser for macular edema secondary to branch retinal vein occlusion: one-year results from a randomized controlled double-blind trial

Abstract: Background: It is not clear whether macular laser combined with anti-vascular endothelial growth factor (VEGF) can reduce the number of anti-VEGF injections in the treatment of macular edema (ME) secondary to branch retinal vein occlusion (BRVO). Our study aimed to investigate the effects of intravitreal ranibizumab with or without macular laser for ME secondary to BRVO and its associated number of anti-VEGF injections. Methods: This is a prospective, randomized, double-blind, monocentric trial.80 patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…All participants signed a standard informed consent form which included information on the potential risks and benefits of the procedure and subsequent management; they could not be identified through this document. We followed the methods of Song et al [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…All participants signed a standard informed consent form which included information on the potential risks and benefits of the procedure and subsequent management; they could not be identified through this document. We followed the methods of Song et al [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…BCVA was reported in 16studies with a total of 1205 RVO patients before and after treatment, including 941 BRVO patients and 264 CRVO patients (Hayashi et al, 2011;Donati et al, 2012;Farese et al, 2014;Rehak et al, 2014;Pielen et al, 2015;Clark et al, 2016;Tadayoni et al, 2016;Tultseva et al, 2017;Callizo et al, 2019;Cao et al, 2019;Goel et al, 2019;Kumar et al, 2019;Terashima et al, 2019;An and Jeong, 2020;Nourinia et al, 2020;Song et al, 2020).The results of random effect model analysis(p < 0.00001,I 2 = 86%) showed that IVI is not inferior to IVI + LPC(WMD = 0.12,95%CI = -3.54-3.78,p = 0.95),neither in BRVO patients (WMD = -2.01,95%CI = -4.37-0.34,p = 0.09),nor in CRVO patients(WMD = 5.82,95%CI = -3.65-15.29,p = 0.23)(Figure 3). The CMT was described in 17 studies with 1101 RVO patients including 989 BRVO patients and 287 CRVO patients (Hayashi et al, 2011;Donati et al, 2012;Farese et al, 2014;Rehak et al, 2014;Pielen et al, 2015;Chhablani et al, 2016;Clark et al, 2016;Tadayoni et al, 2016;Tultseva et al, 2017;Callizo et al, 2019;Cao et al, 2019;Goel et al, 2019;Kumar et al, 2019;Terashima et al, 2019;Nourinia et al, 2020;Song et al, 2020;Thomley et al, 2021).The fixed effect model analysis(p = 0.27,I 2 = 16%)demonstrated that there was no significant difference in CMT between IVI + LPC group and IVI group(WMD = -4.40,95%CI = -21.33-12.53,p = 0.61),whether in BRVO patients p = 0.84) or in CRVO patients(WMD = -21.72,95%CI = -68.89-25.45,p = 0.37)(Figure <...…”
Section: Results Of Meta-analysismentioning
confidence: 99%
“…Recently, some studies (Donati et al, 2012;Farese et al, 2014;Rehak et al, 2014;Tomomatsu et al, 2016;Tultseva et al, 2017;Goel et al, 2019;Terashima et al, 2019;An and Jeong, 2020;Nourinia et al, 2020) have found that, compared with single IVI, the combination of IVI and LPC could improve the prognosis in RVO patients with ME and decrease the number of injections. However, other studies (Hayashi et al, Frontiers in Pharmacology frontiersin.org 2011; Pielen et al, 2015;Chhablani et al, 2016;Tadayoni et al, 2016;Callizo et al, 2019;Cao et al, 2019;Kumar et al, 2019;Song et al, 2020;Thomley et al, 2021) suggested that combination treatment could neither improve the prognosis of patients nor reduce the frequency of IVI, and on the contrary, it has increased the medical burden of RVO patients.…”
Section: Discussionmentioning
confidence: 99%
“…Forty-six patients with BRVO enrolled in Song's study were included. Song's study was a 12-month randomized controlled study assessing the efficacy of intravitreal ranibizumab in patients with ME secondary to BRVO [ 21 ]. This trial conformed to the principles of the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
“…During the follow-up, 3 initial IVR (Lucentis 0.5 mg) injections must be conducted monthly in all affected eyes, and additional injections would be repeated if VA suffered more than 5 letters loss due to disease activity or CRT increased more than 100 μ m compared to the previous visit. All patients had blood pressure (BP) measurement at each visit, and the BP was normal in hypertension patients during the follow-up time [ 21 ].…”
Section: Methodsmentioning
confidence: 99%